Draft Genome Sequence of the Nitrogen-Fixing Rhizobium sullae Type Strain IS123T Focusing on the Key Genes for Symbiosis with its Host Hedysarum coronarium L. - Sablok, Gaurav; Rosselli, Riccardo; Seeman, Torsten; van Velzen, Robin; Polone, Elisa; Giacomini, Alessio; La Porta, Nicola; Geurts, Rene; Muresu, Rosella; Squartini, Andrea (Frontiers in Microbiology, 2017)
The prominent feature of rhizobia is their molecular dialogue with plant hosts. Such interaction is enabled by the presence of a series of symbiotic genes encoding for the synthesis and export of signals triggering organogenetic and physiological responses in the plant. The genome of the R.sullae type strain IS123T nodulating the legume Hedysarum coronarium, was sequenced and resulted in 317 scaffolds for a total assembled size of 7,889,576 bp. Its features were compared with those of genomes from rhizobia representing an increasing gradient of taxonomical distance, from a conspecific isolate (R.sullae WSM1592), to two congeneric cases (R.leguminosarum bv. viciae and R.etli,) and up to different genera within the legume-nodulating taxa. The host plant is of agricultural importance, but, unlike the majority of other domesticated plant species, it is able to survive quite well in the wild. Data showed that that the type strain of R.sullae, isolated from a wild host specimen, is endowed with a richer array of symbiotic genes in comparison to other strains, species or genera of rhizobia that were rescued from domesticated plant ecotypes. The analysis revealed that the bacterium by itself is incapable of surviving in the extreme conditions that its host plant can tolerate. When exposed to drought or alkaline condition, the bacteria depends on its host to survive. Data are consistent with the view of the plant phenotype as the primary factor enabling symbiotic nitrogen fixing bacteria to survive in otherwise limiting environments.